1995
DOI: 10.1002/j.1551-8833.1995.tb06350.x
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic metal polymers: preparation and characterization

Abstract: It is possible to produce stable preparations of partially neutralized aluminum chloride solutions in which cationic aluminum polyelectrolytes predominate, but attempts to produce similar stable preparations containing cationic iron(III) polyelectrolytes were unsuccessful. One method to improve the effectiveness of inorganic metal coagulants in water treatment is to partially neutralize concentrated metal salt solutions prior to their addition to the raw water and thus preform polymeric metal species, the actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
(32 reference statements)
2
36
0
Order By: Relevance
“…It increases only slightly with increase of B. Compared with the results of PFCl (Gray et al, 1995;Tian and Tang, 1989), the same trend of species distribution is observed. The increase of basicity promotes mainly the amount of Fe c with little yield of Fe b .…”
Section: Speciation By Ferron Assaysupporting
confidence: 78%
See 2 more Smart Citations
“…It increases only slightly with increase of B. Compared with the results of PFCl (Gray et al, 1995;Tian and Tang, 1989), the same trend of species distribution is observed. The increase of basicity promotes mainly the amount of Fe c with little yield of Fe b .…”
Section: Speciation By Ferron Assaysupporting
confidence: 78%
“…Because of their superior efficiency and relatively lower cost compared with traditional coagulants such as aluminum or iron salts, IPFs are becoming the main water and wastewater treatment reagents, with production and applications on a large scale in Japan, Russia, West Europe and China presently. The USA has also paid much attention to it in recent years (Tang, 1990;AWWA, 1989;Dentel, 1991;Gray et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the traditional coagulants, IPFs can give markedly improved coagulation effects, and show many advantages such as low dosage, efficient sedimentation, lower sludge volume and flexibility to various water quality conditions [1][2][3]. Among the IPFs, polyaluminum chloride (PACl) is the most efficient, widely applied coagulant and has a mature production technology.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional coagulants, IPFs can give markedly improved coagulation effects, and show many advantages such as low dosage, efficient sedimentation, low sludge volume and flexibility to various water quality conditions (Gray et al, 1995;Tang, 1998;Solomentseva et al, 1999;Wang and Tang, 2001;Wang et al, 2002). Therefore, IPFs have the potential to become the main reagents for water and wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%